2013
DOI: 10.1039/c3nr03790h
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of facet effects on the catalytic activity of Cu2O nanocrystals for efficient regioselective synthesis of 3,5-disubstituted isoxazoles

Abstract: Cubic, octahedral, and rhombic dodecahedral Cu2O nanocrystals bound by respectively {100}, {111}, and {110} facets were successfully employed to catalyze the [3 + 2] cycloaddition reaction for the regioselective synthesis of 3,5-disubstituted isoxazoles. Surfactant-free nanocrystals having the same total surface area were used for the catalysis. Strongly facet-dependent organocatalytic activity has been observed. Rhombic dodecahedra with fully exposed surface copper atoms on the (110) planes are the most effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 34 publications
3
60
0
Order By: Relevance
“…Previously, we demonstrated that Cu 2 O crystals display facet‐dependent electrical conductivity and photocatalytic activity, which involves charge carrier transport into and out of a Cu 2 O crystal through different facets or interfaces. Facet‐dependent organocatalytic properties of Cu 2 O crystals, on the other hand, are considered to be mainly surface‐related properties, because all surface facets exhibit some degrees of catalytic activity . The facet‐dependent optical responses arise in Au‐Cu 2 O crystals because of different degrees of band bending for different surface facets of Cu 2 O, such that different facets can be considered to consist of a thin surface layer with varying refractive indices to tune the plasmonic band positions of the gold cores.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we demonstrated that Cu 2 O crystals display facet‐dependent electrical conductivity and photocatalytic activity, which involves charge carrier transport into and out of a Cu 2 O crystal through different facets or interfaces. Facet‐dependent organocatalytic properties of Cu 2 O crystals, on the other hand, are considered to be mainly surface‐related properties, because all surface facets exhibit some degrees of catalytic activity . The facet‐dependent optical responses arise in Au‐Cu 2 O crystals because of different degrees of band bending for different surface facets of Cu 2 O, such that different facets can be considered to consist of a thin surface layer with varying refractive indices to tune the plasmonic band positions of the gold cores.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that, although high‐index facets that have high‐density atomic edges with corners and plentiful unsaturated active sites are promising for catalysis and sensing applications, those facets are often unstable, and hardly obtained by traditional chemical methods 17, 18, 19, 20, 21, 22, 23. Thus, the shape‐dependent catalysis and sensing behaviours is primarily focused on NCs enclosed by low‐index facets, especially the three basic facets (i. e., the {100}, {111}, and {110} facets) 6, 7, 8, 9, 12, 13, 14, 16, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34. For instance, by employing hydrofluoric acid as a capping agent (CA), H. G. Yang et al34 were the first to obtain uniform anatase TiO 2 single crystals with a high percentage (47%) of highly reactive {001} facets, which possessed promising applications in sensors, solar cells and photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the inexpensive, non‐toxic and abundantly available Cu 2 O nanomaterials, with unique optical and electrical properties,4, 9, 10, 53, 54, 55, 56, 57, 58 have recently aroused general attention, due to their outstanding morphology‐dependent applications in catalysis (gas oxidation,2, 3, 17, 59, 60, 61 CO 2 reduction,62, 63, 64, 65 organocatalysis,14, 24, 32, 40, 50, 66 electrocatalysis,28, 67, 68 and photocatalysis36, 44, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, sensing (gas sensors,8, 79, 80, 81, 82, 83 ion detection,29 and surface‐enhanced Raman scattering (SERS)84, 85, 86, 87, 88, 89, as adsorbents,7, 90 biotoxicity,26, 91, 92 as chemical templates35, 38, 45, 4...…”
Section: Introductionmentioning
confidence: 99%
“…The morphology and structure of the sample were investigated by field emission scanning electron microscopy (FESEM) micrographs. As shown in Figure A and Figure B, the obtained Cu 2 O microcrystals exhibited uniform rhombic dodecahedra shapes with an average particle size of 0.66 µm, which is extremely important to serve as an excellent catalyst for many organic reactions , . To determine the chemical purity of the Cu 2 O microcrystals and identify the chemical state of Cu in the samples, XRD and XPS measurements were performed, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Cu‐based catalysts are used extensively in pyrazoles synthesis. Recently, Cu 2 O cubes, octahedra, and rhombic dodecahedra were employed as catalysts for the direct synthesis of 1,2,3‐triazoles, and 3,5‐disubstituted isoxazoles . And the results verified that rhombic dodecahedra are the most efficient catalysts giving excellent yields.…”
Section: Introductionmentioning
confidence: 85%